Electroplastic effect associated with the dislocation generation in the initially dislocation-free silicon filamentary crystals - Ermakov, A.P.; Darinsky, B.M.; Drozhzhin, A.I. (Functional Materials, 2004)
Experiments on local high-intensity electric current pulse action on mechanical properties of a Si filamentary crystal made it possible to reveal a novel type of electroplastic effect associated with the generation of dislocations.